When colleague got recognized: Third-party’s reaction to witnessing employee recognition - Yang, Tianfei; Jiang, Xia (Frontiers in Psychology, 2023)
Employee recognition, as an incentive method widely used in management practice, plays an important role in the organization. We take the witness side, to explore how the employees who witness the colleague got recognized, would feel and do. Based on the Social Cognitive Theory, this study argues that employee recognition encounter is positively related to work engagement. And, perceived organizational justice and workplace well-being have a chain mediating effect in this pathway. This research adopts the empirical research method by asking the participants to do the weekly survey (four times in one month), and 258 samples are collected. Using SPSS20.0 and its PROCESS macro module, hypotheses are tested. The results indicate: (1) Employees who witness leaders' recognition of colleagues will (a)perceive higher organizational justice and (b)be more engaged in work. (2) Perceived organizational justice will mediate the positive relationship between employee recognition encounter with (a)workplace well-being and (b)work engagement. (3) Perceived organizational justice and workplace well-being will have a chain mediating effect in the path of employee recognition encounter and work engagement.